The Effect of Presumption of Attribution and Nunnation in guiding The Meaning in Some Verses of The Holy Quran (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The Quran has become the starting point for all intellectual and ideological efforts of the Muslims, and the pivot that revolves around the various sciences and studies. Therefore, these sciences have to overlap and communicate among themselves, and benefit each other in fruitful integration. The impact on all branches of Arab Islamic culture was reflected in richness and fertility, which makes the field of research in any science of these sciences fields is spacious and intertwined and difficult.In this research, an attempt is made to shed light on the presumption of Attribution, and its role in weighting one meaning on another meaning in some verses of the Holy Quran. The research also concerned with the definition of Nunnation, and the discussion about its parts, functions and meanings obtained from it. Also, the research dealt with the effect of Nunnation in the guidance of meaning in some verses of the Holy Quran.As a result, it was found that the Attribution is a moral presumption, and the Nunnation is a verbal presumption, and they have a great role in guiding the meaning and interpreting it in some verses of the Holy Quran.